Customer use of virtual channels in multi-channel services: does type of activity matter? - Sousa, Rui (2013)
This paper examines whether customer use of virtual channels varies with the type of service activities (e.g. information search, transactions) they engage in. Based on data from a multichannel bank, we first investigate the impact of customer distance to the nearest branch on the degree of use of virtual channels (internet and phone, aggregated), for different types of activities. Second, when customers do resort to virtual channels to conduct activities, we look at their relative channel preferences (internet vs. phone) for different types of activities. The results inform design decisions about which activities to offer through virtual channels.